Implementasi Layanan untuk Pesan Singkat Menggunakan Perangkat Universal Software Radio Pheripheral (USRP) B210 pada Standar Komunikasi 3GPP Berbasis 4G - Anugraha, Nurhajar; Seliana, Imalda; Soim, Sopian (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Communication technology continues to develop rapidly, now 4G has become a network standard used in various countries. 4G networks offer higher data speeds, lower latency, and greater capacity compared to previous networks. Now, we can exchange information and establish relationships with others without having to meet in person. However, in remote areas and areas with limited networks, there are still problems in using these celluler phones that are poorly understood by people living in remote areas or areas that are not covered by celluler phone networks. For example, the use of very simple cellular phone facilities such as Short Message Service (SMS). OpenBTS is a new part of BTS technology that is very economical both in terms of funds and resources because openBTS is based on opensource software so that it is easily available and anyone can implement this openBTS, and can provide services to communicate such as Short Message Service (SMS) or short messages and can be used as a substitute for telephone facilities in the event of signal interference. For this reason, in this study, the implementation of services for short messages using the Universal Software Radio Peripheral (USRP) B210 device on 4G-based 3GPP communication standards. The hardware used is USRP B210.